Transforming Growth Factor (TGF) β and Endometrial Vascular Maturation - Lu, Qinsheng; Sun, Dingqian; Shivhare, Sourima Biswas; Hou, Huomei; Bulmer, Judith N.; Innes, Barbara A.; Hapangama, Dharani K.; Lash, Gendie E. (Frontiers in Cell and Developmental Biology, 2021)
Appropriate growth and development of the endometrium across the menstrual cycle is key for a woman’s quality of life and reproductive well-being. Recurrent pregnancy loss (RPL) and heavy menstrual bleeding (HMB) affect a significant proportion of the female population worldwide. These endometrial pathologies have a significant impact on a woman’s quality of life as well as placing a high economic burden on a country’s health service. An underlying cause for both conditions is unknown in approximately 50% of cases. Previous research has demonstrated that aberrant endometrial vascular maturation is associated with both RPL and HMB, where it is increased in RPL but reduced in HMB. TGFβ1 is one of the key growth factors that regulate vascular maturation, by inducing phenotypic switching of vascular smooth muscle cells (VSMCs) from a synthetic phenotype to a more contractile one. Our previous data demonstrated an increase in TGFβ1 in the endometrium of RPL, while others have shown a decrease in women with HMB. However, TGFβ1 bioavailability is tightly controlled, and we therefore sought to perform an extensive immunohistochemical analysis of different components in the pathway in the endometrium of normal controls, women with HMB or RPL. In addition, two in vitro models were used to examine the role of TGFβ1 in endometrial vascular maturation and endothelial cell (EC):VSMC association. Taken all together, the immunohistochemical data suggest a decrease in bioavailability, receptor binding capacity, and signaling in the endometrium of women with HMB compared with controls. In contrast, there is an increase in the bioavailability of active TGFβ1 in the endometrium of women with RPL compared with controls. Endometrial explants cultured in TGFβ1 had an increase in the number of vessels associated with contractile VSMC markers, although the total number of vessels did not increase. In addition, TGFβ1 increased EC:VSMC association in an in vitro model. In conclusion, TGFβ1 is a key regulator of endometrial vascular maturation and could be considered as a therapeutic target for women suffering from HMB and/or RPL.